2018
DOI: 10.1016/j.redox.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous DNA damage to the nuclear genome promotes senescence, redox imbalance and aging

Abstract: Accumulation of senescent cells over time contributes to aging and age-related diseases. However, what drives senescence in vivo is not clear. Here we used a genetic approach to determine if spontaneous nuclear DNA damage is sufficient to initiate senescence in mammals. Ercc1-/∆ mice with reduced expression of ERCC1-XPF endonuclease have impaired capacity to repair the nuclear genome. Ercc1-/∆ mice accumulated spontaneous, oxidative DNA damage more rapidly than wild-type (WT) mice. As a consequence, senescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 102 publications
(127 reference statements)
1
94
0
1
Order By: Relevance
“…Taken together, our data demonstrate that Ercc1 − /∆ mice share a pattern of cellular senescence that is consistent and commensurate with that observed in aged WT mice. The DNA repair‐deficient Ercc1 − /∆ mice accumulate endogenous DNA damage faster than WT mice (Robinson, ; Wang et al, ), and we now show that this corresponds with the accelerated accumulation of senescent cells. This supports the conclusions that spontaneous, endogenous DNA damage drives cellular senescence in vivo with natural aging and that the Ercc1 − /∆ mice truly age in an accelerated manner.…”
Section: Discussionsupporting
confidence: 69%
“…Taken together, our data demonstrate that Ercc1 − /∆ mice share a pattern of cellular senescence that is consistent and commensurate with that observed in aged WT mice. The DNA repair‐deficient Ercc1 − /∆ mice accumulate endogenous DNA damage faster than WT mice (Robinson, ; Wang et al, ), and we now show that this corresponds with the accelerated accumulation of senescent cells. This supports the conclusions that spontaneous, endogenous DNA damage drives cellular senescence in vivo with natural aging and that the Ercc1 − /∆ mice truly age in an accelerated manner.…”
Section: Discussionsupporting
confidence: 69%
“…Ercc1 −/Δ mice are a model for human Cockayne and COF syndromes, which are rare progeroid syndromes with extremely short lifespans (Gregg et al, 2011;Vermeij, Dollé, et al, 2016). Increases in both cellular senescence and apoptosis in Ercc1 −/Δ mice have been reported (Niedernhofer et al, 2006;Robinson et al, 2018;Takayama et al, 2014;Tilstra et al, 2012;Weeda et al, 1997). These two processes are partly interconnected by common molecular pathways (Childs et al, 2014), but how they interact is not clear.…”
Section: Senescent Cells Are Generally Resistant To Apoptosis Often Duementioning
confidence: 99%
“…In addition, suppression of the GH/IGF1 axis is also observed in the mouse model defective for both Csb and Xpa functions, whose phenotype largely mimics the CS clinical features . Of note, a recent study in the Ercc1 Δ /− mice has shown that these animals accumulate oxidative DNA damage more rapidly than age‐matched wild‐type mice and that oxidative stress appears to be due, at least in part, to mitochondrial‐derived ROS …”
Section: Molecular Basis Of Overlap Syndromesmentioning
confidence: 99%